Comparison of Vaginal Microbiota Profiles in Patients With Endometriosis and Without Endometriosis - Sef Zani Meria; Yuad, Haviz; Putra, Andani Eka (Andalas Obstetrics And Gynecology Journal, 2025)
Introduction: Endometriosis is a complex gynecological disease affect 10% of women in reproductive age, involving inflammation and immune regulation. Diversity of vaginal microbiota is an integral part of vaginal microecology with vaginal anatomy, endocrine system and local vaginal immunity. The disruption in microecology, dysbiosis, is known to trigger inflammatory diseases. The relationship between vaginal dysbiosis and endometriosis remains controversial Objective: To determine the comparison of vaginal microbiota profiles in patients with and without endometriosis Method: The study was case-control design on patients with and without endometriosis at Dr. M. Djamil Hospital, conducted from December 2023 to June 2024 at Dr. M. Djamil Hospital Polyclinic and the Center for Infectious Disease Diagnostic and Research Laboratory. The diagnosis of endometriosis was confirmed via ultrasonography and histology. Microbiota were measured with miSeq Illumina Next Generation Sequencing. A comparison of microbiota profiles was carried out using the Mann-Whitney test. Results: There were 40 respondents, with endometriosis (n=20) and without endometriosis (n=20). At the phylum level, the vaginal microbiota profile in the endometriosis group was dominated by Firmicutes, Proteobacteria, Actinobacteria, and Bacteroidetes, while in without endometriosis group dominated by Firmicutes, Actinobacteria, Bacteroidetes, and Proteobacteria. At the genus level, the endometriosis group was dominated by Lactobacillus sp., Desulfovibrio sp., Flavobacterium sp., and Gardnerella sp., while without endometriosis group were Lactobacillus sp., Prevotella sp., Desulfovibrio sp., and Bifidobacterium sp. There was no difference in the abundance of microbiota (p>0.05) Conclusion: There was no difference in the abundance of microbiota between endometriosis group and without endometriosis group.   Keywords: Endometriosis, dysbiosis, vaginal microbiota, Lactobacillus, Flavobacterium, Firmicutes, Proteobacteria